Facteurs alimentaires et environnementaux de risque du cancer du rhino-pharynx au Maroc et leur répartition géographique - Soumia Ammor; Abdellatif Baali; Mohamed Cherkaoui; Annie Hubert (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The study of a group of 409 patients affected by NPC (nasopharyngeal carcinoma) using 394 people as a control group has shown that this cancer was predominant in men (sex-ratio = 1.80), particularly in the younger population (10.5% of patients were aged less than 20 years). A logistic regression analysis has shown that preservation of food in brine, along with living in an agricultural environment and having contact with toxic compounds seem to be statistically significant factors related to NPC. However, we did not find a statistically significant relationship with other food factors such as khlii and quaddid, probably due to a decrease or irregularity in their consumption. Furthermore, subdividing Morocco into three zones of variable incidence of NPC (North-Rif-Oriental, Center-Middle Atlas, Haouz-South) revealed the existence of a south-north gradient of exposure to presumed risk factors, essentially bad living conditions, food preservation agents and poor hygiene.